Adverse Consequences to Assisting Victims of Campus Violence: Initial Investigations Among College Students - Krauss, Alison (Journal of interpersonal violence, 2021)
Despite growing interest in the use of bystander education programs to address the problems of sexual and relationship violence on college campuses, little knowledge exists on adverse consequences experienced by students intervening as a bystander. The current study examined the prevalence and correlates of adverse consequences of bystander intervention in two samples of first-year college students. In Study 1, 281 students completed a measure of negative consequences experienced when acting as a bystander to help someone at risk of sexual assault, relationship abuse, or stalking. Efficacy for bystander behavior was also assessed. Approximately one third of the students (97/281) reported having tried to help someone who had been at risk of violence during the previous academic year. Of these, approximately 17% (16/97) reported experiencing a negative consequence from having tried to help. Experiencing negative consequences was associated with lower levels of bystander efficacy. In Study 2, conducted at a different university, 299 students completed measures of negative consequences resulting from intervening as a bystander and efficacy for bystander behavior. Students also participated in virtual-reality simulations that provided opportunities to intervene as a bystander. Again, approximately one third of the students (99/299) reported having tried to help someone at risk of violence. Of these, 20% (20/99) reported experiencing a negative consequence. Two of the adverse consequences (physically hurt, got into trouble) were negatively associated with bystander efficacy and observed effectiveness of bystander behavior in the virtual simulations. Results of exploratory analyses suggest that training in bystander intervention might reduce the likelihood of experiencing adverse consequences.